Manajemen strategi untuk meningkatkan kualitas pendidikan di SDN Ngaglik 2 Kota Batu - Ihtada, Hayyin Misro (Maliki Interdisciplinary Journal, 2024)
The aim of this research is to identify the application of strategic management to improve the quality of education at SDN Ngaglik 2 Batu City to improve the quality of education, because currently many educational institutions do not implement strategic management optimally, causing various obstacles to occur. This research was conducted at SDN Ngaglik 2 Batu City. This research uses qualitative methods with a field study approach. Data sources come from observations, interviews and documentation. The findings from this research explain that there are various activities to carry out Strategic Management planning at SDN Ngaglik 2, Batu city, including: Formulating and establishing a vision and mission; Considering the existence of obstacles, threats, opportunities and solutions in solving problems; improve the quality of educators and learning. SDN 2 Ngaglik Kota Batu carries out evaluation activities through; Special meetings between principals, deputy principals and teachers; Special meeting of the principal with the committee; as well as other meetings that bring up useful things.